Symptoms of Estrogen Deficiency and Quality of Life - Beinhofnerová, Darina; Moravcová, Markéta (University of Pardubice, 2017)
Introduction: The quality of life of every individual is influenced by many different factors. For women in menopause, estrogen deficiency is undoubtedly one of these factors. Estrogen deficit leads to a series of symptoms, which may affect their quality of life to some extent. In the clinical practice, it is important to have a tool to assess the quality of life that is practical and is able not only to assess the quality of life. Aim: The aim of the research was to determine whether and to what extent the symptoms of estrogen deficiency occur in women during menopause and how they affect their quality of life. Method: The survey ran from July to October 2016 in a medical facility in Zlín. The research involved 284 women aged 45–60 years who suffered from the symptoms of estrogen deficiency. The incidence and severity of symptoms were assessed using the printed form of the Czech version of the Menopause Rating Scale questionnaire. Results: The respondents reported mostly mild or no problems. Only a few of the respondents rated the intensity of some problems as intolerable. Total score points to the fact that most women have high quality of life. Conclusion: Given that women currently spend up to one third of their life in the postmenopausal period, it is very important to deal with these symptoms and address them. If women suffer from estrogen deficiency symptoms, it is necessary to evaluate their intensity and impact for which the Menopause Rating Scale is a suitable tool.
Keywords: estrogen deficiency; menopause; menopause rating scale; quality of life